Research Article Seasonal variation of the bacterial diversity residing in sediments of Tam Giang lagoon, Central Viet Nam - Tran Thi Kim, Dung; Do, Hoang Giang; Pham Viet, Cuong; Tran Thi, Hong (Vietnam Journal of Science and Technology, 2025)
Bacterial communities within sediment play a critical role in lagoon ecosystem nutrient cycling. Moreover, the sediments diversity of Vietnamese lagoons remains largely unexplored. Tam Giang Lagoon is one of the largest lagoons in the world, the largest in Southeast Asia and Vietnam. Therefore, it contains very high biodiversity potential. This study aimed to analyze variation between dry and wet seasons in bacterial diversity within the Tam Giang Lagoon, Central Vietnam. Sediment samples were collected for subsequent Illumina sequencing of the V3-V4 regions of the 16S rRNA gene to elucidate community composition. Mothur software was ultilized for the analysis and identification the Operational Taxonomic Units (OTUs). Pseudomonadota was the most dominant phylum in the lagoon in both seasons, followed by Verrucomicrobiota, Acidobacteriota, and Chloroflexota. Interestingly, there are bold variations of bacterial abundance between dry and wet season samples at all taxonomic levels. This study shows that different climatic conditions between the two seasons can change the physical and chemical environment in the lagoon, thereby greatly affecting the bacterial population structure. Thus, based on the results of this study, it is possible to identify beneficial bacterial populations in each season to optimize the breeding environment, improve water quality, reduce environmental pollution, and increase biological productivity in the lagoon ecosystem